DESIGN FEATURES OF INTERNET PROJECTS FOR SALES AND PROMOTION ON BUILDING MATERIALS MARKET - E. S. Marchenko; O. S. Safin; L. A. Ostrinskaya (Вестник СибАДИ, 2017)
Nowadays there is a need in automating the process of interaction of the organization with the consumer. Internet space allows attaining gooed results applying different e-commerce models, the correct choice of model and the way of realization will lead to good indexes in the end. It’s important to remember, that e-commerce project lifecycle unites not only activities for designing and integration existing systems, but also different techniques of digital marketing, that optimize promotion goods on the market. Design features of internet projects examined by the example of the real company.